Impact of Toll-like receptor 2 expression in renal allograft rejection - Hoffmann, Ute; Bergler, Tobias; Rihm, Munhie; Pace, Claudia; Krüger, Bernd; Jung, Bettina; Reinhold, Stephan W.; Farkas, Stefan; Rümmele, Petra; Krämer, Bernhard; Banas, Bernhard (Nephrology, dialysis, transplantation, 2011)
Background. An important role of TLR2 has been shown in various experimental models of renal ischaemia/reperfusion injury. To study the expression of TLR2 in renal allograft rejection systematically, we established an experimental rat transplantation model.Methods. TLR2 expression was analysed in 99 human renal allograft biopsies, and in rat allografts at Day 6 and 28 after experimental renal transplantation. To discriminate whether regulation of TLR2 was following immunological processes after allogeneic transplantation or was a consequence from ischaemia/reperfusion injury, control animals subjected to syngeneic transplantation or to ischaemia/reperfusion damage were also investigated.Results. TLR2 mRNA was significantly elevated in rat allografts with acute rejection on Day 6 and decreased spontaneously towards Day 28. TLR2 induction correlated with renal function and TLR2 excretion in the urine of transplanted rats. TLR2 staining was also significantly increased in human allografts with acute rejection. TLR2 protein could be localized in tubular epithelial cells and vascular endothelial cells, and in CD68- and CD4-positive infiltrating cells.Conclusions. TLR2 is markedly up-regulated in both experimental and human acute renal allograft rejection. Our data suggest a role for TLR2 during allogen-dependent graft damage after renal transplantation.
Advance access publication 13 July 2010
Gesehen am 11.07.2022